1998
DOI: 10.1074/jbc.273.51.34284
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Allosteric Regulation of the Rod cGMP Phosphodiesterase Activity by the Helical Domain of Transducin α Subunit

Abstract: The G protein ␣ subunit (G␣) is composed of two distinct folding domains: a GTP-binding Ras-like domain and an ␣ helical domain (HD). We have recently reported that the helical domain (HD t ) of the vertebrate visual transducin ␣ subunit (G␣ t ) synergizes activation of retinal cyclic GMP phosphodiesterase (PDE) by activated G␣ t (Liu, W., and Northup, J. K., (1998) Proc. Natl. Acad. Sci. U. S. A. 95, 12878 -12883). Here, we examine the molecular basis for this HD-based signaling regulation, and we provide a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 58 publications
(74 reference statements)
0
16
0
Order By: Relevance
“…In other cases, ␣T* was assayed in the presence of rhodopsin and G␤␥ (f) or in the absence of rhodopsin (E), and ␣T*(R238E) was assayed in the presence of rhodopsin and G␤␥ (OE). The results are representative of three experiments (31)(32)(33), it was attractive to consider that interactions between Switch 3 and the helical domain might be essential for effector regulation. Since we already had shown that changing the position of the helical domain relative to the GTPase domain can influence GDP-GTP exchange, we also wondered whether disrupting interactions between Switch 3 and the helical domain might impact G␣ activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other cases, ␣T* was assayed in the presence of rhodopsin and G␤␥ (f) or in the absence of rhodopsin (E), and ␣T*(R238E) was assayed in the presence of rhodopsin and G␤␥ (OE). The results are representative of three experiments (31)(32)(33), it was attractive to consider that interactions between Switch 3 and the helical domain might be essential for effector regulation. Since we already had shown that changing the position of the helical domain relative to the GTPase domain can influence GDP-GTP exchange, we also wondered whether disrupting interactions between Switch 3 and the helical domain might impact G␣ activation.…”
Section: Discussionmentioning
confidence: 99%
“…1b), which is in the phosphate-binding P-loop lying just upstream from the beginning of the large helical domain, whereas in the activated (GTP␥S-bound) ␣T subunit, Arg-238 contacts both Glu-39 and Gln-143 of the helical domain. It has been suggested that the helical domain of G␣ subunits plays a role in mediating the regulation of target/effectors, and in the particular case of ␣T, may be essential for the stimulation of PDE activity (31)(32)(33). Thus, we wanted to see whether disruption of the apparent links between the conserved Arg-238 in Switch 3 and Glu-39 and/or Gln-143 might compromise ␣T activation and/or its ability to bind and regulate the PDE.…”
Section: The Conformationally Sensitive Switch 3 Region Of ␣T Influenmentioning
confidence: 99%
“…In addition to switch III residues shown to participate in G t␣ -PDE␥ binding, class-specific residues g91, g142, g143, and g144, found in the helical domain, are exposed on the surface of G ␣ . A recent study reported the surprising result that the helical domain alone can increase the activity of PDE in a G ␣ -specific manner (47,48). However, the helical domain is almost entirely devoid of ET surface signal, with the exception of residues g91 and g142-g144.…”
Section: A General Effector Binding Surface On G␣mentioning
confidence: 99%
“…PDE activity was assayed by a phosphate release assay as described previously (16). Protein assay was performed routinely by the Bradford assay (17).…”
Section: Immunoblotting Detection Of Various Subunits Of Pde and Tranmentioning
confidence: 99%